2023
DOI: 10.5935/0004-2749.2022-0274
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miR-210-3p in the aqueous humor of patients with age-related cataracts and its effect on human lens epithelial cell injury induced by hydrogen peroxide

Abstract: The regulatory effect of microRNA on diseases has been confirmed. This study aimed to evaluate the expression of microRNA-210-3p in age-related cataracts and assess the effect of abnormal miR-210-3p expressions on H 2 O 2 -induced SAR01/04 cells. Methods: Reverse-transcription quantitative polymerase chain reaction method was performed to assess the levels of miR-210-3p in aqueous humor samples. Receiver operating characteristic analysis was employed to assess the discrimination ability of miR-210-3p between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…In biological membranes, ROS produced during I/R reacted with unsaturated fats to produce MDA, the end product of LPO [17][18] . In addition to being a biological marker of tissue damage, MDA was also one of the most important markers of oxidative damage [19][20] . In this study, it was revealed that there was a significant increase in MDA level in the eye tissue of the I/R group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In biological membranes, ROS produced during I/R reacted with unsaturated fats to produce MDA, the end product of LPO [17][18] . In addition to being a biological marker of tissue damage, MDA was also one of the most important markers of oxidative damage [19][20] . In this study, it was revealed that there was a significant increase in MDA level in the eye tissue of the I/R group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%